The Effect of Burnout on Turnover Intention With Work-Life Balance as a Mediating Variable - Iswanto, Budi; Setyaningrum, Retno Purwani (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
Burnout is a psychological condition that can lead to an employee's intention to leave the organization, known as turnover intention. Recent studies suggest that work-life balance may play a mediating role in this relationship. This study aims to examine the effect of burnout on turnover intention with work-life balance as a mediating variable. A quantitative method was applied using a questionnaire distributed to employees of a private company, with 86 respondents selected from a population of 108 through incidental sampling. The data were analyzed using Structural Equation Modeling with SmartPLS 3.0. The results show that burnout has a positive and significant effect on turnover intention (β = 0.601; t = 4.765; p < 0.001). However, burnout has a non-significant effect on work-life balance (β = 0.118; p = 0.151), and work-life balance also does not significantly affect turnover intention (β = 0.212; p = 0.088). Consequently, work-life balance does not mediate the relationship between burnout and turnover intention. These findings highlight the importance for organizations to focus directly on managing burnout as a priority in reducing turnover intention among employees.